1984
DOI: 10.1002/cyto.990050215
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of the binding of eleven lectins to human T‐ and B‐cells and to human T‐ and B‐cell lines

Abstract: The relative surface binding of 11 lectins to human peripheral blood T‐ and B‐lymphocytes, to Molt‐4 and JM T‐cell lines, and to 6410 and NC37 B‐cell lines was determined by flow cytometry. The lectins from Lens culinaris (LCA), Ricinus communis (RCA), Arachis hypogaea (PNA), Abrus precatorius (APA), Ulex europaeus (UEA‐F), Sarothamnus scoparius (SAS‐F), Helix pomatia (HPA), Phaseolus coccineus (L‐PHA), Glycine max (SBA), and Triticum vulgare (WGA) were fluoresceinated and incubated with living, formaldehyde‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Flow cytometric analysis of lectin binding has been used to detect cell surface changes, to determine lymphocyte subpopulations under normal and pathological conditions, and to determine the stage of differentiation or development of certain cells of mammalian species (Madewell et al, 1984;Malin-Berdel et al, 1984). The present results demonstrate that these techniques can be applied to the avian system with consistent results.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Flow cytometric analysis of lectin binding has been used to detect cell surface changes, to determine lymphocyte subpopulations under normal and pathological conditions, and to determine the stage of differentiation or development of certain cells of mammalian species (Madewell et al, 1984;Malin-Berdel et al, 1984). The present results demonstrate that these techniques can be applied to the avian system with consistent results.…”
Section: Discussionsupporting
confidence: 62%
“…These analyses have been performed on both cell suspensions and tissue sections with assays including cell agglutination, histochemical staining, and, more recently, flow cytometric analysis (Madewell et al, 1984;Malin-Berdel et al, 1984. In a previous study (Greenfield et al, 1986), histochemical staining with peroxidase labelled concanavalin A (con A) was used to detect a pathological change in a small population of leukocytes within the bursa of Fabricus. With infectious bursal disease virus (IBDV) infection, cells that appeared to be macrophages were found to rearrange into foci within the bursa.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, using flow cytometric analysis, Malin-Berdel et al reported on the relative surface binding of 11 lectins (including ConA) to human peripheral blood T and B cells and human T-and B-cell lines. Only lectin from Lens culinaris (LCA), which preferentially bound to the two Bcell lines, exhibited selective binding to the undifferentiated cells [15]. Malin-Berdel et al [15] postulated that the conflicting results possibly reflect the influence of cell volume on the evaluation of cell-bound fluorescence [16] or may be due to the use of much higher lectin concentrations [17] and different reaction conditions that make additional binding sites accessible [18].…”
Section: Discussionmentioning
confidence: 99%
“…Lectins are carbohydrate-binding proteins which have been extensively used for detection and characterization of glycoproteins. Lectin binding is not only specific to individual sugar structure, but also appears to depend on local steric interactions in the immediate molecular neighborhood of the target carbohydrates [24,33,35]. Lectins have been used to characterize cell surface glycans because of their specificity in terms of branching, linkage and terminal structure of glycans [36,37].…”
Section: Discussionmentioning
confidence: 99%